Electroformation of electrocatalytically active hydrous oxide layers on a Co-Ni amorphous alloy under pulsating electrolysis - Triaca, Walter Enrique (1993)
A hydrous oxide film can be grown on a CO₅₀Ni₂₅SI₁₅B₁₀ amorphous alloy through the application of a periodic perturbing potential routine in alkaline solution. The optimal parameters of the square wave potential signal are determined. The oxide film is a precursor of a Co-Ni spinel as concluded from voltammetry, i.r. spectroscopy, XPS and SEM micrography. The catalytic activity of the oxide layer for the oxygen evolution reaction is demonstrated.